Superior thermotolerance in young versus adult rats undergoing heat stroke is associated with age-related differences in intestinal barrier integrity and heat shock protein responses - Cai, Yuanhao; Lei, Lei; Chen, Jikuai; Zhao, Xi; Chen, Juelin; Zhou, Jiawei; Pei, Yankun; Wang, Yawei; Gong, Yitong; You, Jianyao; Cao, Yangyang; Song, Muge; et al. (Frontiers in Cell and Developmental Biology, 2026)
Heat stroke (HS) is a life-threatening condition exacerbated by rising global temperatures, with children identified as a particularly vulnerable population. Despite this, basic research on age-related differences in thermotolerance remains limited. In this study, we established a high-temperature and high-humidity exposure model with real-time core body temperature (CBT) monitoring to investigate thermotolerance in young versus adult rats. The results showed that young rats exhibited prolonged CBT plateau phases and delayed HS onset, indicating enhanced thermotolerance compared to adult rats. This was accompanied by significantly milder multi-organ injury and reduced intestinal barrier damage. Young rats displayed lower serum levels of D-lactate and intestinal fatty acid-binding protein, better-preserved intestinal epithelial ultrastructure, and higher expression of tight junction proteins such as ZO-1, Occludin, and E-cadherin. Moreover, young rats showed elevated expression of heat shock proteins (HSP40 and HSP70) in intestinal tissues, which likely contributed to improved barrier integrity and cellular protection. These findings suggest that enhanced intestinal barrier stability and robust HSP responses underlie the superior thermotolerance observed in young rats. However, despite their physiological advantages, infants and young children often suffer poor HS outcomes due to behavioral limitations and caregiver negligence, especially in enclosed environments such as parked vehicles. This highlights the critical need for enhanced caregiver awareness, improved pediatric emergency response training, and preventive strategies to mitigate pediatric HS risk.